2016
DOI: 10.1515/cerce-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Among Some Rice Genotypes with Different Drought Tolerance based on SSR Markers

Abstract: Rice is the most important food crop for the developing world. Hence, identifying rice genotypes to drought tolerance for using as donors in breeding is one of the most important challenges for rice research. Therefore, Molecular markers are useful tools to determine genetic diversity and identifying rice genotypes to drought tolerance. In the present study, A number of 41 rice genotypes with different drought tolerance from different geographic locations were evaluated for genetic diversity by using 15 SSR ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Yadav et al [ 49 ] reported higher genetic diversity and PIC values in some Indian rice germplasm using trait linked SSR markers. In this study, nearly 70% (17) markers had greater than 0.4085 gene diversity and PIC values, strongly indicating that majority of the markers used in current research are moderate to highly informative for evaluating genetic diversity [ 50 ]. These results are further supported by higher inbreeding coefficient values (range; 0.7052–1.0000) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 98%
“…Yadav et al [ 49 ] reported higher genetic diversity and PIC values in some Indian rice germplasm using trait linked SSR markers. In this study, nearly 70% (17) markers had greater than 0.4085 gene diversity and PIC values, strongly indicating that majority of the markers used in current research are moderate to highly informative for evaluating genetic diversity [ 50 ]. These results are further supported by higher inbreeding coefficient values (range; 0.7052–1.0000) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 98%
“…The mean Fst values for all loci and between the two clusters were found to be 0.7786 and 0.1987 respectively indicating very high genetic differentiation among loci and among the clusters. Based on SSR analysis, there were seventeen highly informative markers (PIC> 0.50), viz., RM1, RM154, RM131, RM135, RM72, RM171, RM287, RM3825, RM246, RM260, RM525, RM219, RM223, RM8094, RM493, RM3412 and RM169; two informative markers (PIC between 0.25 and 0.50), RM153, RM125, and RM302; and two slightly informative markers (PIC< 0.25), RM315 and RM443 [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific advances have allowed the use of genome-wide molecular markers for the identification of genetic alterations, allowing the discrimination of genotypes (cultivars or varieties) of the same species with tolerance-related characteristics to several environmental stresses [ 50 , 51 , 52 , 53 , 54 , 55 ]. Studies with this scope have given subsidies to plant breeding programs [ 56 , 57 ], but genetic variability in oil palm individuals with and without FY symptoms still deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%